1999
DOI: 10.1073/pnas.96.26.14807
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid induces proteasome-dependent degradation of retinoic acid receptor α (RAR α ) and oncogenic RAR α fusion proteins

Abstract: Analyzing the pathways by which retinoic acid (RA) induces promyelocytic leukemia͞retinoic acid receptor ␣ (PML͞RAR␣) catabolism in acute promyelocytic leukemia (APL), we found that, in addition to caspase-mediated PML͞RAR␣ cleavage, RA triggers degradation of both PML͞RAR␣ and RAR␣. Similarly, in non-APL cells, RA directly targeted RAR␣ and RAR␣ fusions to the proteasome degradation pathway. Activation of either RAR␣ or RXR␣ by specific agonists induced degradation of both proteins. Conversely, a mutation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
290
5
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 339 publications
(326 citation statements)
references
References 43 publications
27
290
5
4
Order By: Relevance
“…It has been demonstrated that the effect of RA, in terms of inducing or inhibiting degradation of RARa, is cell type specific (30)(31)(32). We observed that ATRA caused a decrease in RARa levels in the cultured neurons, and this decrease was not altered by p38 MAPK inhibition.…”
Section: Discussionsupporting
confidence: 52%
“…It has been demonstrated that the effect of RA, in terms of inducing or inhibiting degradation of RARa, is cell type specific (30)(31)(32). We observed that ATRA caused a decrease in RARa levels in the cultured neurons, and this decrease was not altered by p38 MAPK inhibition.…”
Section: Discussionsupporting
confidence: 52%
“…Cette sumoylation, ainsi que d'autres modifications post-traductionnelles (notamment des phosphorylations ou acétylations), pourraient influencer le rôle de RXRa dans la répression et/ou l'activation basale des gènes cibles de PML-RARa [17]. Enfin, le traitement par l'AR des LAP entraîne in vivo la perte de l'ancrage de PML-RARa et RXRa sur les gènes cibles ainsi que leur dégradation [21,25], en parallèle de l'activation de ces gènes. [26].…”
Section: Revuesunclassified
“…À ce titre, les cellules transformées ex vivo par un mutant de PML-RARa incapable de fixer RXRa présentent des caractéristiques monocytaires après traitement à l'AR. Ceci pourrait refléter la plus grande disponibilité de RXRa du fait de l'absence de dégradation de la protéine non complexée à PML-RARa [25]. Par ailleurs, la présence de RXRa dans le complexe PML-RARa permet de traiter des LAP résistantes aux traitements à l'AR via l'activation de la voie de l'AMPc et des réxinoïdes, ce mécanisme reflétant la…”
Section: Rôle Fonctionnel De Rxra Dans L'oncogenèseunclassified
“…L'As 2 O 3 induit la phosphorylation de SMRT/NcoR par la voie MAPK, aboutissant à la dissociation de SMRT/NcoR de PML/RARα et à la différenciation cellulaire [2]. De plus, l'As 2 O 3 et l'AR induisent la dégradation par le protéasome de PML/RARα en ciblant respectivement PML et RARα, ce qui permet à nouveau la formation des corps nucléaires PML [12,13]. Ainsi, PML et RARα retrouvent leur fonction entraînant la reprise des fonctions normales de la cellule (Figure 2).…”
Section: Effets Généraux De L'arsenic De L'antiquité à Nos Joursunclassified